Companion to contemporary Black British culture - Donnell, Alison, 1966- (Routledge, 2002)
The Companion to Contemporary Black British Culture is the first comprehensive reference book to provide multidisciplinary coverage of the field of black cultural production in Britain. The publication is of particular value because despite attracting growing academic interest in recent years, this field is still often subject to critical and institutional neglect. For the purpose of the Companion, the term 'black' is used to signify African, Caribbean and South Asian ethnicities, while at the same time addressing the debates concerning notions of black Britishness and cultur.